All-organic polymer S-type heterojunction photocatalytic material as well as preparation method and application thereof
By forming an organic conjugated polymer film in situ on the surface of carbon nitride, forming an all-organic polymer S-type heterojunction material, the problems of low carrier separation efficiency and insufficient redox capacity in existing semiconductor photocatalytic materials are solved, and efficient photocatalytic performance improvement is achieved.
Patent Information
- Application Number
- CN202411692855.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In the photocatalytic process, existing semiconductor photocatalytic materials have serious recombination of photogenerated electrons and holes and slow kinetic transfer speeds, and cannot guarantee that photogenerated carriers have strong oxidation and reduction capabilities.
Using all-organic polymer S-type heterojunction material, through the composite of carbon nitride as a support and organic conjugated polymer, the coupling reaction between alkynyl groups is catalyzed by cuprous chloride to form a uniform and stable organic conjugated polymer film in situ on the surface of carbon nitride, forming a tightly contact heterointerface to improve carrier separation efficiency.
It significantly improves the carrier separation efficiency and the oxidation and reduction capabilities of the catalyst, effectively improves the photocatalytic performance, especially in the production of hydrogen peroxide by about 3 times.
Smart Images

Figure CN119633900A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor photocatalytic materials, and in particular to an all-organic polymer S-type heterojunction photocatalytic material and a preparation method and application thereof. Background Art
[0002] With the increasing energy shortage and environmental crisis, photocatalysis using sunlight as green energy can directly realize the conversion of solar energy into chemical energy, which is an efficient and sustainable way of energy conversion. Nevertheless, the current single semiconductor material used for photocatalytic production is often affected by the serious recombination of photogenerated electrons and holes and the slow kinetic transfer rate. At the same time, due to the limitation of fixed band structure, it is impossible to ensure that the photogenerated carriers have strong oxidation and reduction ability. It is still challenging to obtain an efficient photocatalytic system with advantages such as wide visible light response, efficient photogenerated carrier separation / transport separation, and strong redox ability. Therefore, constructing a suitable heterojunction is one of the most promising ways to solve such challenges. Unlike the previously reported type II heterojunction photocatalyst, the newly developed S-type heterojunction is mainly composed of two parts, a reduced photocatalyst and an oxidized photocatalyst, in a way that the energy bands are intertwined. The unique S-type charge transfer path allows meaningless electrons and holes to recombine, and meaningful electrons and holes to be effectively separated. Not only can the separation efficiency of carriers be enhanced, but also the catalyst can have stronger oxidation and reduction capabilities, effectively improving the photocatalytic performance.
[0003] In recent years, the application of S-type heterojunction materials in the field of photocatalysis has gradually become a research hotspot. Compared with the traditional all-inorganic heterojunction, a series of inorganic / organic semiconductor S-type heterojunctions have been reported recently to improve the carrier separation efficiency and optimize the photocatalytic performance. Nevertheless, the fixed energy band position of inorganic semiconductors makes the screening of materials with matching energy band positions a time-consuming step. Therefore, the rational design and efficient screening of semiconductors with suitable energy band positions are huge challenges in the construction of S-type heterojunction photocatalytic materials. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide an all-organic polymer S-type heterojunction photocatalytic material which constructs an S-type heterojunction by an organic polymer and a carbon nitride carrier to improve the catalytic activity; the second purpose of the present invention is to provide a method for preparing the all-organic polymer S-type heterojunction photocatalytic material; the third purpose of the present invention is to provide an application of the all-organic polymer S-type heterojunction photocatalytic material.
[0005] Technical solution: The all-organic polymer S-type heterojunction photocatalytic material described in the present invention includes a carrier and an organic polymer grown on the surface of the carrier, and the organic monomer is polymerized on the carbon nitride surface to form an all-organic polymer S-type heterojunction, and the organic monomer is 1,4-diethynylbenzene (DEB), 2,5-diethynylpyridine (DEP) or 3,6-diethynylpyridazine (DED).
[0006] Preferably, the mass ratio of the organic monomer to the carrier carbon nitride is 3: 1 to 5: 1. As the proportion of the organic monomer increases, the photocatalytic hydrogen peroxide production performance of the all-organic polymer S-type heterojunction photocatalytic material first increases and then decreases.
[0007] Preferably, the carbon nitride is porous carbon nitride. There are many pore structures distributed in the porous carbon nitride. These continuous pores can greatly increase the specific surface area of the material, which is conducive to better in-situ polymerization of organic monomers on the porous carbon nitride; and more pores are conducive to obtaining more active sites, which can promote the effective improvement of photocatalytic performance.
[0008] The method for preparing the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0009] (1) adding carbon nitride and a catalyst into a polar alkaline solution and mixing them evenly;
[0010] (2) placing an organic monomer in the mixed solution prepared in step (1) to cause a polymerization reaction, thereby in situ generating an all-organic polymer S-type heterojunction photocatalytic material.
[0011] Preferably, the catalyst is cuprous chloride.
[0012] Preferably, the polymerization reaction temperature is 40-80°C.
[0013] Preferably, the polymerization reaction time is 4 to 8 hours.
[0014] Preferably, the polar solvent in the polar alkaline solution is pyridine.
[0015] Preferably, the polar base in the polar base solution is piperidine.
[0016] The invention discloses an application of the all-organic polymer S-type heterojunction photocatalytic material in photocatalytic production of hydrogen peroxide.
[0017] Invention mechanism: The present invention uses carbon nitride (CN) as a carrier and cuprous chloride as a catalyst to catalyze the in-situ polymerization of organic monomers on the surface of carbon nitride to generate a fully organic polymer heterojunction material. The selected organic monomers are 1,4-diethynylbenzene (DEB), 2,5-diethynylpyridine (DEP) or 3,6-diethynylpyridazine (DED). The Cu generated by cuprous chloride in a polar alkaline solution + and Cu 2+ , catalyzing the Glaser coupling reaction between alkyne groups to obtain a uniform and stable organic conjugated polymer film on the carbon nitride surface.
[0018] Carbon nitride and an organic conjugated polymer are selected for composite, wherein the energy band position of the organic conjugated polymer is adjustable and can be adjusted to match the energy band position of carbon nitride by changing the molecular structure, thereby forming an all-organic polymer S-type heterojunction, which enables a higher charge separation efficiency within the molecule.
[0019] The organic conjugated polymer material is directly grown in situ on carbon nitride, forming a closely contacted heterointerface with carbon nitride, which greatly promotes the migration rate of photogenerated carriers; secondly, carbon nitride and organic conjugated polymers form an S-type heterojunction material through an interlaced band structure, which effectively improves the carrier separation efficiency; finally, the ratio of carbon nitride and organic conjugated polymers can be optimized to give it the best catalytic performance in photocatalytic reactions.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) Carbon nitride is selected as a carrier and a composite of an organic conjugated polymer, wherein the organic conjugated polymer can be adjusted to match the energy band position of carbon nitride by changing the molecular structure to form an all-organic polymer S-type heterojunction, so that the intramolecular charge transfer rate is faster; (2) By optimizing the ratio of carbon nitride and the organic conjugated polymer, it has the best catalytic performance in the photocatalytic reaction; (3) The preparation method has mild process conditions, simple operation, low cost, and can be used for large-scale production; (4) Compared with traditional carbon nitride, the efficiency of the prepared in-situ grown all-organic polymer S-type heterojunction photocatalytic material in producing hydrogen peroxide is increased by about 3 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the catalyst preparation process of the present invention;
[0022] Figure 2 is a scanning electron microscope image of porous carbon nitride;
[0023] Figure 3 This is a scanning electron microscope image of poly(1,4-diethynylbenzene);
[0024] Figure 4This is a scanning electron microscope image of pDEB-CN-4 in Example 2;
[0025] Figure 5 This is a transmission electron micrograph of pDEB-CN-4 in Example 2;
[0026] Figure 6 is the EDX spectrum of pDEB-CN-4 in Example 2;
[0027] Figure 7 X-ray diffraction spectra (XRD) of Examples 1-3 and Comparative Examples 1 and 2;
[0028] Figure 8 To test the photocatalytic activity of composite materials with different proportions of DEB monomers;
[0029] Fig. 9 To test the photocatalytic activity of composite materials with different proportions of DEP monomers;
[0030] Fig.10 To test the photocatalytic activity of composite materials with different proportions of DED monomers;
[0031] Fig.11 To test the photocatalytic activity of composite materials with different organic monomers;
[0032] Fig.12 In the figure, a is the photocurrent response test of the samples prepared in Example 2 and Comparative Examples 1 and 2; b is the electrochemical impedance test of the corresponding samples. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with embodiments.
[0034] Example 1
[0035] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0036] (1) Preparation of porous carbon nitride
[0037] Weigh 5 g of urea and place it in a 20 mL covered porcelain boat, cover it with a lid, place it in a tube furnace, heat it from room temperature to 550 ° C at a heating rate of 5 ° C / min, and keep it at 550 ° C for 4 hours. After the reaction is completed, cool it naturally to room temperature, take it out, and grind it evenly in a quartz mortar to obtain porous carbon nitride powder;
[0038] (2) Weigh 20 mg of the porous carbon nitride powder obtained in step (1) and 250 mg of cuprous chloride into a glass reaction bottle, then weigh 50 μL of piperidine and 5 mL of pyridine and add them to the glass reaction bottle, and disperse them evenly by ultrasonication to obtain a mixed solution;
[0039] (3) Weighing 60 mg of DEB, adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDEB-CN-3 all-organic polymer photocatalytic material.
[0040] Example 2
[0041] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0042] Step (1) and step (2) are the same as in Example 1.
[0043] (3) Weighing 80 mg of DEB, adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDEB-CN-4 all-organic polymer photocatalytic material.
[0044] Example 3
[0045] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0046] Step (1) and step (2) are the same as in Example 1.
[0047] (3) Weighing 100 mg of DEB, adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDEB-CN-5 all-organic polymer photocatalytic material.
[0048] Example 4
[0049] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0050] Step (1) and step (2) are the same as in Example 1.
[0051] (3) Weighing 60 mg of DEP and adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDEP-CN-3 all-organic polymer photocatalytic material.
[0052] Example 5
[0053] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0054] Step (1) and step (2) are the same as in Example 1.
[0055] (3) Weighing 80 mg of DEP and adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDEP-CN-4 all-organic polymer photocatalytic material.
[0056] Example 6
[0057] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0058] Step (1) and step (2) are the same as in Example 1.
[0059] (3) Weighing 100 mg of DEP and adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDEP-CN-5 all-organic polymer photocatalytic material.
[0060] Example 7
[0061] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0062] Step (1) and step (2) are the same as in Example 1.
[0063] (3) Weighing 60 mg of DED and adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDED-CN-3 all-organic polymer photocatalytic material.
[0064] Example 8
[0065] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0066] Step (1) and step (2) are the same as in Example 1.
[0067] (3) Weighing 80 mg of DED and adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDED-CN-4 all-organic polymer photocatalytic material.
[0068] Example 9
[0069] The preparation method of the all-organic polymer S-type heterojunction photocatalytic material of the present invention comprises the following steps:
[0070] Step (1) and step (2) are the same as in Example 1.
[0071] (3) Weighing 100 mg of DED and adding it to the mixed solution obtained in step (2), placing the reaction system in an oven at 60° C. for 6 h; after the reaction, cooling the reaction system to room temperature, and then washing the obtained product with pyridine, dichloromethane, and methanol in sequence, and finally drying the product to obtain the pDED-CN-5 all-organic polymer photocatalytic material.
[0072] Comparative Example 1
[0073] The difference between Comparative Example 1 and Example 1 is that only step (1) is completed to obtain the ground powder, which is marked as CN.
[0074] Comparative Example 2
[0075] The difference between Comparative Example 2 and Example 1 is that the powder obtained in step (1) is not added in step (2), and the remaining steps are the same as those in Example 1. The obtained product is labeled as pDEB.
[0076] Comparative Example 3
[0077] The difference between Comparative Example 3 and Example 4 is that the powder obtained in step (1) is not added in step (2), and the remaining steps are the same as those in Example 4. The obtained product is labeled as pDEP.
[0078] Comparative Example 4
[0079] The difference between Comparative Example 4 and Example 7 is that the powder obtained in step (1) is not added in step (2), and the remaining steps are the same as those in Example 1. The obtained product is labeled as pDED.
[0080] Morphological characterization
[0081] (1) Physical characterization of the samples prepared in Examples 1 to 3, Comparative Example 1 and Comparative Example 2 was performed. The results are as follows: Figures 2 to 7 shown.
[0082] Depend on Figure 2It can be seen that the porous carbon nitride prepared in Comparative Example 1 is a nanosheet layered uniform stack, and an obvious pore structure can be observed on the nanosheet.
[0083] Depend on Figure 3 It can be seen that the poly(1,4-diethynylbenzene) prepared in Comparative Example 2 exhibits irregular fibrous distribution.
[0084] Depend on Figure 4 It can be seen that the prepared pDEB conjugated polymer grows uniformly on the porous carbon nitride.
[0085] Depend on Figure 5 Under high-resolution transmission electron microscopy, it was clearly observed that the surface of the porous carbon nitride nanosheets was covered with continuous and uniform fibrous poly(1,4-diethynylbenzene).
[0086] Figure 6 The medium energy dispersive X-ray spectroscopy element mapping diagram shows that the C and N elements are evenly distributed in the pDEB-CN-4 all-organic polymer S-type heterojunction material in Example 2.
[0087] Figure 7 For porous carbon nitride, poly (1,4-diethynylbenzene) and pDEB-CN-3 / 4 / 5 in Examples 1 to 3, it can be seen that the original conjugated polymer has no obvious diffraction peak, while the composite material in the example has a diffraction peak corresponding to the 002 crystal plane of carbon nitride at 27.4°, which indicates that the pDEB-CN-3 / 4 / 5 all-organic polymer composite material was successfully synthesized.
[0088] Performance Characterization
[0089] (1) Catalytic activity test of different ratios of DEB monomers
[0090] Under xenon lamp irradiation (λ≥420nm, 60mW cm -2 ) conditions, 15 mg of the materials synthesized in Example 1, Example 2, Example 3 and Comparative Example 2 were taken as catalysts, added into 30 mL of pure water, O2 was continuously introduced into the water, and the sample liquid was taken every 20 min for detection in an ultraviolet spectrophotometer. The test results are shown in FIG. Figure 8 shown.
[0091] Figure 8 It can be seen that different ratios of DEB to CN will cause differences in the photocatalytic performance of the synthesized composite materials. Under the irradiation condition of λ≥420nm, the concentration of hydrogen peroxide produced by pDEB at 100min is 149μM, while under the conditions of DEB to CN mass ratio of 3:1, 4:1 and 5:1, the concentrations of hydrogen peroxide produced at 100min are 176μM, 205μM and 154μM respectively. The performance is best when the mass ratio of DEB to CN is 4:1, and the performance of other ratios is lower than that of the samples synthesized under this condition.
[0092] (2) Catalytic activity test of different proportions of DEP monomers
[0093] Under xenon lamp irradiation (λ≥420nm, 60mW cm -2 ) conditions, 15 mg of the materials synthesized in Example 4, Example 5, Example 6 and Comparative Example 3 were taken as catalysts in 30 mL of pure water, O2 was continuously introduced into the water, and the sample liquid was taken every 20 min for detection in an ultraviolet spectrophotometer. The test results are shown in FIG. Fig. 9 shown.
[0094] Fig. 9 It can be seen that different ratios of DEP to CN will cause differences in the photocatalytic performance of the synthesized composite materials. Under the irradiation condition of λ≥420nm, the concentration of hydrogen peroxide produced by pDEP at 100min is 41μM, while under the conditions of DEP to CN mass ratios of 3:1, 4:1 and 5:1, the concentrations of hydrogen peroxide produced at 100min are 70μM, 117μM and 58μM respectively. The performance is best when the mass ratio of DEP to CN is 4:1, and the performance of other ratios is lower than that of the samples synthesized under this condition.
[0095] (3) Catalytic activity test of DED monomers at different ratios
[0096] Under xenon lamp irradiation (λ≥420nm, 60mW cm -2 ) conditions, 15 mg of the materials synthesized in Example 7, Example 8, Example 9 and Comparative Example 4 were taken as catalysts and added to 30 mL of pure water. O2 was continuously introduced into the water. Samples were taken every 20 min and tested in an ultraviolet spectrophotometer. The test results are shown in FIG. Fig.10 shown.
[0097] Fig.10 It can be seen that different ratios of DED and CN will cause differences in the photocatalytic performance of the synthesized composite materials. Under the irradiation condition of λ≥420nm, the concentration of hydrogen peroxide produced by pDED at 100min is 18μM, while under the conditions of DED and CN mass ratios of 3:1, 4:1 and 5:1, the concentrations of hydrogen peroxide produced at 100min are 37μM, 41μM and 32μM respectively. The performance is best when the mass ratio of DED to CN is 4:1, and the performance of other ratios is lower than that of the samples synthesized under this condition.
[0098] (4) Effects of different organic monomers on catalytic performance
[0099] In order to explore the effects of different designed organic monomers on the construction of all-organic polymer S-type heterojunction photocatalytic materials, three organic monomers with different molecular structures were used to form composite materials with carbon nitride.-2 ) conditions, a photocatalytic production of hydrogen peroxide test was conducted. 15 mg of the materials synthesized in Example 2, Example 5 and Example 8 were taken as catalysts in 30 mL of pure water, O2 was continuously introduced into the water, and the sample liquid was taken every 20 min for detection in an ultraviolet spectrophotometer. The test results are shown in FIG. Fig.11 shown.
[0100] like Fig.11 As shown, under xenon lamp irradiation (λ≥420nm, 60mW cm -2 ) conditions, the pDEB-CN-4 of Example 2, the pDEP-CN-4 of Example 5, and the pDED-CN-4 of Example 8 produced hydrogen peroxide concentrations of 205 μM, 117 μM, and 41 μM, respectively, at 100 min. The performance of the synthesized pDEB-CN-4 all-organic polymer S-type heterojunction photocatalytic material is much higher than that of pDEP-CN-4 and pDED-CN-4. This proves the superiority of the monomer structure selected in the present invention for constructing an S-type heterojunction composite material.
[0101] (5) Effect of constructing S-type heterojunction on catalytic performance
[0102] In order to explore the effect of constructing an all-organic polymer S-type heterojunction on the catalytic performance of the catalyst, a three-electrode system was used to perform photocurrent response and electrochemical impedance tests on an electrochemical workstation, with Ag / AgCl as the reference electrode, Pt wire as the working electrode, and FTO uniformly coated with the catalyst as the working electrode. The test results are shown in Figure 2. Fig.12 shown.
[0103] like Fig.12 As shown, under xenon lamp irradiation (λ≥420nm, 60mW cm -2 ) conditions, compared with the CN of Comparative Example 1 and the pDEB of Comparative Example 2, the pDEB-CN-4 of Example 2 showed the largest photocurrent density. In addition, Fig.12 As shown, in the electrochemical impedance test, pDEB-CN-4 of Example 2 showed the smallest electrochemical impedance. This indicates that the S-type heterojunction constructed by the present invention can effectively improve the separation efficiency of photogenerated carriers, thereby facilitating the improvement of the performance of photocatalytic production of hydrogen peroxide.
Claims
1. An all-organic polymer S-type heterojunction photocatalytic material, characterized in that: The material comprises a carrier and an organic polymer grown on the surface of the carrier. The organic monomer is polymerized on the surface of carbon nitride to form an all-organic polymer S-type heterojunction. The organic monomer is 1,4-diethynylbenzene, 2,5-diethynylpyridine or 3,6-diethynylpyridazine.
2. The all-organic polymer S-type heterojunction photocatalytic material according to claim 1, characterized in that: The mass ratio of the organic monomer to the carrier carbon nitride is 3:1 to 5:
1.
3. The all-organic polymer S-type heterojunction photocatalytic material according to claim 1, characterized in that: The carbon nitride is porous carbon nitride.
4. A method for preparing the all-organic polymer S-type heterojunction photocatalytic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) adding carbon nitride and a catalyst into a polar alkaline solution and mixing them evenly; (2) placing an organic monomer in the mixed solution prepared in step (1) to cause a polymerization reaction, thereby in situ generating an all-organic polymer S-type heterojunction photocatalytic material.
5. The method for preparing the all-organic polymer S-type heterojunction photocatalytic material according to claim 4, characterized in that: The catalyst is cuprous chloride. 6 . The method for preparing an all-organic polymer S-type heterojunction photocatalytic material according to claim 4 , wherein the polymerization reaction temperature is 40 to 80° C. 7 . The method for preparing an all-organic polymer S-type heterojunction photocatalytic material according to claim 4 , wherein the polymerization reaction time is 4 to 8 hours. 8 . The method for preparing an all-organic polymer S-type heterojunction photocatalytic material according to claim 4 , wherein the polar solvent in the polar alkaline solution is pyridine. 9 . The method for preparing an all-organic polymer S-type heterojunction photocatalytic material according to claim 4 , wherein the polar base in the polar base solution is piperidine.
10. Use of the all-organic polymer S-type heterojunction photocatalytic material according to any one of claims 1 to 3 in photocatalytic production of hydrogen peroxide.
Citation Information
Patent Citations
Polymer-based antimicrobial compositions and methods of use thereof
CN109714968A
Preparation method of heterojunction photo-catalyst by compounding titanium dioxide and carbon nitride
CN110404572A
Cellulose biochar loaded graphite phase carbon nitride catalytic material as well as preparation method and application thereof
CN117019196A
Preparation method of hydrophilic conjugated polymer composite hydroxyl-rich carbon nitride photocatalyst
CN117563664A
Preparation method and application of hollow sphere structure conjugated microporous polymer TiO2 composite membrane material
CN118161983A
Cited By
Organic semiconductor heterojunction nanoparticle-carbon nitride composite photocatalyst and application thereof
CN120984333A